MR molecular imaging of brain cancer metabolism using hyperpolarized (13)C magnetic resonance spectroscopy - Najac, Chloé (Top Magn Reson Imaging, 2016)
Metabolic reprogramming is an important hallmark of cancer. Alterations in many metabolic pathways support the requirement for cellular building blocks that are essential for cancer cell proliferation. This metabolic reprogramming can be imaged using magnetic resonance spectroscopy (MRS). (1)H MRS can inform on alterations in the steady-state levels of cellular metabolites, but the emergence of hyperpolarized (13)C MRS has now also enabled imaging of metabolic fluxes in real-time, providing a new method for tumor detection and monitoring of therapeutic response. In the case of glioma, preclinical cell and animal studies have shown that the hyperpolarized (13)C MRS metabolic imaging signature is specific to tumor type and can distinguish between mutant IDH1 glioma and primary glioblastoma. Here, we review these findings, first describing the main metabolic pathways that are altered in the different glioma subtypes, and then reporting on the use of hyperpolarized (13)C MRS and MR spectroscopic imaging (MRSI) to probe these pathways. We show that the future translation of this hyperpolarized (13)C MRS molecular metabolic imaging method to the clinic promises to improve the noninvasive detection, characterization, and response-monitoring of brain tumors resulting in improved patient diagnosis and clinical management.